Pleiotropic effects of laminar flow and statins depend on the Krüppel-like factor-induced lncRNA MANTIS. (21st June 2019) - Leisegang, Matthias S; Bibli, Sofia-Iris; Günther, Stefan; Pflüger-Müller, Beatrice; Oo, James A; Höper, Cindy; Seredinski, Sandra; Yekelchyk, Michail; Schmitz-Rixen, Thomas; Schürmann, Christoph; Hu, Jiong; Looso, Mario; et al.
Abstract: Aims: To assess the functional relevance and therapeutic potential of the pro-angiogenic long non-coding RNA MANTIS in vascular disease development. Methods and results: RNA sequencing, CRISPR activation, overexpression, and RNAi demonstrated that MANTIS, especially its Alu-element, limits endothelial ICAM-1 expression in different types of endothelial cells. Loss of MANTIS increased endothelial monocyte adhesion in an ICAM-1-dependent manner. MANTIS reduced the binding of the SWI/SNF chromatin remodelling factor BRG1 at the ICAM-1 promoter. The expression of MANTIS was induced by laminar flow and HMG-CoA-reductase inhibitors (statins) through mechanisms involving epigenetic rearrangements and the transcription factors KLF2 and KLF4. Mutation of the KLF binding motifs in the MANTIS promoter blocked the flow-induced MANTIS expression. Importantly, the expression of MANTIS in human carotid artery endarterectomy material was lower compared with healthy vessels and this effect was prevented by statin therapy. Interestingly, the protective effects of statins were mediated in part through MANTIS, which was required to facilitate the atorvastatin-induced changes in endothelial gene expression. Moreover, the beneficial endothelial effects of statins in culture models (spheroid outgrowth, proliferation, telomerase activity, and vascular organ culture) were lost upon knockdown of MANTIS. Conclusion: MANTIS is tightly regulated by the transcription factors KLF2 and KLF4 and limits the ICAM-1 mediated monocyte adhesion to endothelial cells and thus potentially atherosclerosis development in humans. The beneficial effects of statin treatment and laminar flow are dependent on MANTIS.